THE IMPROVEMENT OF SOFT SOIL LAYER FOR TOLL ROAD EMBANKMENT ON JAVA NORTH SHORE A STUDY CASE ON JALAN TOL PEJAGAN PEMALANG - Dito Senna Hardiman; Rinda Karlinasari (International Conference on Coastal and Delta Areas, 2015)
To deal with soft soil, of Prefabricated Vertical Drain (PVD), Prefabricated Horizontal Drain (PHD) and geotextile were carrying out at Pejagan-Pemalang Toll Road Project. On construction, to monitor the settlement of embankment occurring due to the consolidation of soft soil, a set of settlement plates, piezometer and inclinometer were used. Settlement plate was used to monitor vertical settlement, piezometer was used to monitoring the change of excess pore pressure, and inclinometer was used to monitor the horizontally shifting embankment toe. All the monitoring instrumentations can then explain the PVD performance to accelerate the embankment consolidation.Keywords: prefabricated vertical drain, settlement plate, embankment consolidation